Penerapan Manajemen Pendidikan Islam Berbasis Worldview Qur’ani di SD IT Al Kautsar Cikarang: Implementation of Islamic Education Management Based on the Qur'anic Worldview at SD IT Al Kautsar Cikarang - Kholid Suhaemi; Iwan Kosasih; Asep Furqonuddin (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
This study aims to analyze the implementation of Islamic education management based on the Qur'anic worldview at SD IT Al Kautsar Cikarang. The background of the study stems from the need for integrated Islamic schools to not only integrate the national and religious curricula, but also to make the Qur'anic vision a philosophical and operational framework for educational management. The study used a qualitative case study approach through in-depth interviews, observations, and analysis of official school documents. Informants consisted of eight parties, including the principal, tahfidz teachers, and homeroom teachers, using a purposive sampling technique. The results of the study show five forms of application of the Qur'anic worldview in educational management: (1) integration of Qur'anic values ??in learning strategies, including strengthening morals and memorization programs; (2) planning that combines academic targets with tahfidz and literacy-numeracy programs; (3) organization and leadership based on a spiritual-transformative model; (4) integration of Qur'anic verses in general subjects and implementation of the morning Qur'an program; and (5) evaluation that includes academic, character, and memorization aspects through digital report cards. This research contributes to the development of Islamic education management studies by showing how the Qur'anic worldview can be operationalized in the managerial practices of integrated Islamic elementary schools.